Pancreaticoduodenectomy as an option for treating a hemodynamically unstable traumatic pancreatic head injury with a pelvic bone fracture in Korea: a case report - Sung Yub Jeong; Yoonhyun Lee; Hojun Lee (Journal of Trauma and Injury)
Pancreatic trauma occurs in 0.2% of patients with blunt trauma and 5% of severe abdominal injuries, which are associated with high mortality rates (up to 60%). Traumatic pancreatoduodenectomy (PD) has significant morbidity and appreciable mortality owing to complicating factors, associated injuries, and shock. The initial reconstruction in patients with severe pancreatic injuries aggravates their status by causing hypothermia, coagulopathy, and acidosis, which increase the risk for early mortality. A staging operation in which PD follows damage control surgery is a good option for hemodynamically unstable patients. We report the case of a patient who was treated by staging PD for an injured pancreatic head.